Epistemologi dan Pendekatan-pendekatan Hermeneutika Hasan Hanafi - Anshory, Ali Ridwan; Salsabila, Hanna (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This research aims to explore Hasan Hanafi's hermeneutics in interpreting the Al-Qur'an through a liberation and emancipatory interpretation approach. Hasan Hanafi wants to describe humans in their capacity as humans, involving linguistic, historical, social and geographical aspects. Hanafi's motivation comes from concerns about the crisis of interpretive orientation and the weakening of epistemological reasoning. By combining phenomenology, Marxism, Ushul Fiqih, and hermeneutics, Hanafi created a practical hermeneutic theory to provide solutions to the problems of Muslims, creating a normative-ideological basis for fighting repression, exploitation, and injustice. The recommendation from this research is to continue further research regarding Hasan Hanafi's practice of interpreting the verses of the Al-Qur'an.